Decline in Antibody Concentration 6 Months After Two Doses of SARS-CoV-2 BNT162b2 Vaccine in Solid Organ Transplant Recipients and Healthy Controls - Hamm, Sebastian Rask; Møller, Dina Leth; Pérez-Alós, Laura; Hansen, Cecilie Bo; Pries-Heje, Mia Marie; Heftdal, Line Dam; Hasselbalch, Rasmus Bo; Fogh, Kamille; Madsen, Johannes Roth; Almagro Armenteros, Jose Juan; Knudsen, Andreas Dehlbæk; Poulsen, Johan Runge; et al. (Frontiers in Immunology, 2022)
Background: Previous studies have indicated inferior responses to SARS-CoV-2 vaccination in solid organ transplant (SOT) recipients. We examined the development in anti-receptor binding domain (RBD) IgG after two doses of BNT162b2b in SOT recipients six months after vaccination and compared to immunocompetent controls. Methods: We measured anti-receptor binding domain (RBD) IgG after two doses of BNT162b2 in 200 SOT recipients and 200 matched healthy controls up to six months after first vaccination. Anti-RBD IgG concentration and neutralizing capacity of antibodies were measured at first and second dose of BNT162b2 and two and six months after first dose. T-cell responses were measured six months after first dose. Results: In SOT recipients geometric mean concentration (GMC) of anti-RBD IgG increased from first to second dose (1.14 AU/mL, 95% CI 1.08-1.24 to 11.97 AU/mL, 95% CI 7.73-18.77) and from second dose to two months (249.29 AU/mL, 95% CI 153.70–385.19). Six months after the first vaccine anti-RBD IgG declined (55.85 AU/mL, 95% CI 36.95-83.33). At all time-points, anti-RBD IgG was lower in SOT recipients than in controls. Fewer SOT recipients than controls had a cellular response (13.1% vs. 59.4%, p<0.001). Risk factors associated with humoral non-response included age (RR 1.23 per 10 year increase, 95% CI 1.11-1.35, p<0.001), being within one year from transplantation (RR 1.55, 95% CI 1.30-1.85, p<0.001 ), treatment with mycophenolate (RR 1.54, 95% CI 1.09-2.18, p=0.015), treatment with corticosteroids (RR 1.45, 95% CI 1.10-1.90, p = 0.009), kidney transplantation (RR 1.70, 95% CI 1.25-2.30, p=0.001), lung transplantation (RR 1.63, 95% CI 1.16-2.29, p = 0.005) and de novo non-skin cancer comorbidity (RR 1.52, 95% CI, 1.26-1.82, p<0.001). Conclusion: Immune response to BNT162b2 are inferior in SOT recipients compared to healthy controls, and studies aiming to determine the clinical impact of inferior vaccine responses are warranted.